2013
DOI: 10.1002/mbo3.95
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of a lectin‐like Burkholderia cenocepacia protein

Abstract: Bacteriocins of the LlpA family have previously been characterized in the γ-proteobacteria Pseudomonas and Xanthomonas. These proteins are composed of two MMBL (monocot mannose-binding lectin) domains, a module predominantly and abundantly found in lectins from monocot plants. Genes encoding four different types of LlpA-like proteins were identified in genomes from strains belonging to the Burkholderia cepacia complex (Bcc) and the Burkholderia pseudomallei group. A selected recombinant LlpA-like protein from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…In this respect, PyoL1 and its homologues resemble other Pseudomonas LlpAs, lacking a discernable secretion motif, whereas the members of the second group are most likely substrates of the Sec translocon, similarly to Xanthomonas and Burkholderia LlpAs (Ghequire et al. 2012b , 2013b ).…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, PyoL1 and its homologues resemble other Pseudomonas LlpAs, lacking a discernable secretion motif, whereas the members of the second group are most likely substrates of the Sec translocon, similarly to Xanthomonas and Burkholderia LlpAs (Ghequire et al. 2012b , 2013b ).…”
Section: Resultsmentioning
confidence: 99%
“…One peculiar characteristic of these LlpAs is their overlapping activity spectrum: a strain may be sensitive to more than one LlpA, even if sequence homology between the amino‐terminal domains of the LlpAs involved is barely present. Tandem‐MMBL bacteriocins were also retrieved in two Xanthomonas pathovars (Ghequire et al ., ) and in Burkholderia cenocepacia (Ghequire et al ., ), equally displaying genus‐specific activity.…”
Section: Lectin‐like Bacteriocinsmentioning
confidence: 99%
“…cenocepacia LlpAs has been reported for B. ambifaria, B. anthina, B. cenocepacia, and B. metallica [19]. B. cenocepacia TAtl-371's antibacterial activity against other Bcc species (B. multivorans, B. dolosa, B. stabilis and B. pyrrocinia) was determined by our research group (data not shown).…”
Section: Genome Propertiesmentioning
confidence: 61%
“…cenocepacia TAtl-371 genome contains two genes encoding a lectin-like bacteriocin, namely LlpA. These tandemly organized genes are homologues to llpA-like genes found in other B. cenocepacia strains [19]. The antimicrobial activity of B.…”
Section: Genome Propertiesmentioning
confidence: 99%